Comparing the efficiency of Denture brush and Ordinary brush in complete Denture cleaning - Fayaz, Amir; Shakerian, Mohaddeseh; Ansari, Ghassem (Novelty in Biomedicine, 2013)
Please cite this article as: Fayaz A, Shakerian M, Ansari GH. Comparing the Efficiency of Denture brush and Ordinary brush in complete Denture cleaning. Novel Biomed 2013;1(2):62-65. Background & objective: Denture cleansing is a key element in retaining mucosa free of any inflammation. However, many denture users usually ignore this important factor. This investigation was designed to compare the efficacy of a denture brush and an ordinary brush in cleansing process of complete dentures. Materials & Methods: A group of 31 individuals aged 44-76 years were included in this study. Each patient was then instructed to use the denture brush for a period of 4 weeks while an ordinary brush was to be used for the following 4 weeks. Dentures were photographed and evaluated at every two week intervals using a computer photographic software assessment method. Pictures were compared using the image tool for plaque remaining on the denture surfaces. Student t-test was used to analyse data collected. Results: Comparison of the brush type efficacy at 2 and 4 weeks did not show any significant difference ( P>0.05 ), however , clinical evaluation indicated that denture brush leaves much less plaque bio-film compare to the ordinary one, with mean plaque traced at 6.88 to 9.24 in 4 weeks. Conclusion: There were no significant differences found between the two brushes’ efficacy, with clinical evaluation significantly in favor of denture brush.